SYSTEM DESIGN IN RENTAL VCD XYZ WITH APPLICATION VISUAL FOXPRO - Duhri Hartono; Jalinas Jalinas, SKom, MM (Jurnal Sistem Informasi, 2002)
VCD rental lot that the average transaction was huge, but still manage occupancydata manually, such as data management members, VCD data, borrowing data andreturns data in making its report Seta. This will cause delays in the information to bereceived by members and leaders. The process of managing data on VCD oldimpressed very simple but nevertheless still errors and delays in the requiredinformation. VCD rental services in addition to a collection of movies available isalso worth noting the quality of service.With the existence of a good rental system and supported by an integrated programand integrated applications that are expected there will be no delay in information tobe received well by members and leaders as well as data errors associated with datamembers, VCD data, borrowing data and restorations.Program is carried applications used in the design of this DVD rental system, builtusing Microsoft Visual FoxPro software is so easy to operate. With this program thisapplication will make the provision of information needed by leaders and memberswill be more easily and quickly handled so that it will improve the quality of theVCD rental service and will ultimately increase the number of rental transactions.